SMART PLAG WEB TOOL - Basavashri Hudge; Dr Kishan Singh (International Educational Journal of Science and Engineering, 2026)
This paper introduces an online originality verification framework that quantifies content overlap through an adjustable cutoff parameter. The framework accepts document uploads or raw text entry, then categorizes content originality dynamically based on computed match ratios.